Eficiência dos sistemas Outrigger em edifícios altos de concreto armado - Goldani, Daniel (2021)
This work brings a bibliographic research on the theoretical functioning of Outrigger Systems in reinforced concrete tall buildings, explores examples of buildings where the system was used, as well as presenting a wide testing of structural models. The efficiency of systems with 1, 2 and 3 levels of hardened floors with Outriggers was verified, comparing them with structural models that do not use the system. The effects of wind action on the structure of a 273.5 m high, 78-story building were analyzed, with an slenderness ratio of 11:1. The behavior of the Outriggers was analyzed, acting in conjunction with various shear wall core arrangements. A control spreadsheet was set up with information on global stability, horizontal displacement at the top, requests at the base of the building, steel and concrete consumption and cost data. Facing the results of dozens of structural models for the building, it is identified that the Outriggers Systems are efficient in mitigating the action of the wind: They reduce the drift at the top of the building and reduce the bending moment acting at the base of the core. In addition, the Outriggers reduce the building’s reinforcing steel consumption.